Exploring the Nexus between Leadership Styles, Employee Engagement, and Organizational Performance a Multidimensional Review - Badie’ Alhmoud; Al-Kasasbeh, Omar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This multidimensional literature review explores the complex interplay between leadership styles, employee engagement, and organizational performance, providing a comprehensive analysis across various sectors such as healthcare, education, IT, and non-profits. It critically examines how transformational, transactional, and servant leadership paradigms distinctly influence employee engagement levels and, subsequently, organizational outcomes. The review delves into the mechanisms through which leadership practices shape organizational culture, employee motivation, and an environment conducive to innovation and high performance. It further investigates the mediating and moderating roles of innovation climate, knowledge sharing, and high-performance work systems in the relationship between leadership styles and organizational effectiveness. By synthesizing empirical findings and theoretical insights, this review highlights the strategic importance of leadership in enhancing employee engagement and propelling organizational performance. The findings suggest that transformational and servant leadership are particularly effective in creating engaging work environments that drive superior organizational results. This study underscores the necessity for leaders to adopt adaptable, people-centered approaches that foster employee well-being and development, thereby contributing to the achievement of strategic objectives and sustained organizational success. The review concludes with recommendations for future research, emphasizing the exploration of emerging trends and contextual factors that may influence the dynamic relationship between leadership, employee engagement, and organizational performance.